Molecular variation of lipoxygenase-associated genes in grain of commercial Mexican soybean cultivars - López , Mónica; Sifuentes, Ana; Paredes, Francisco; Maldonado, Nicolás; Gill, Homar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Lipoxygenase enzymes encoded by the Lox1, Lox2 and Lox3 genes play a crucial role in soybean grain, particularly in the development of off-flavors. Understanding molecular variation within Lox genes is essential for the improvement of soybean organoleptic traits. This study investigated the genetic variation in the internal regions of the Lox1, Lox2, and Lox3 genes in mature grain of commercially grown soybean cultivars in Mexico. Genomic DNA from a diverse panel of Mexican soybean cultivars was analyzed using resequencing techniques and in-silico analysis. Single nucleotide polymorphisms (SNP) within the Lox1, Lox2, and Lox3 genes were identified and characterized. The findings indicated that Lox3 gene displayed lower genetic variability compared to Lox1 and Lox2 genes, specifically, was identified a total of 26 SNPs in the Lox1 gene, 11 SNPs in the Lox2 gene, and 5 SNPs in the Lox3 gene among the examined cultivars. A non-synonymous SNP variant of the C/C genotype located in exon 6 of the Lox2 gene was associated with a destabilizing effect on the lipoxygenase 2 enzyme in the Guayparime S-10 and Huasteca 300 cultivars. These findings provide insights into the molecular variation of lipoxygenase-associated genes in Mexican soybean cultivars.